A fluorescent microporous crystalline dendrimer discriminates vapour molecules. Issue 20 (21st February 2018) - Nakajima, Sae; Albrecht, Ken; Kushida, Soh; Nishibori, Eiji; Kitao, Takashi; Uemura, Takashi; Yamamoto, Kimihisa; Bunz, Uwe H. F.; Yamamoto, Yohei
Abstract : The surprising crystalline self-assembly of a conjugated dendrimer with exciting optical and sensing properties. Abstract : A self-assembled crystalline microporous dendrimer framework (MDF) exhibits novel turn-on and ratiometric fluorescence upon exposure to solvent vapours. The donor–acceptor character, combined with the large surface area (>650 m 2 g −1 ), allows the MDF to discriminate vapours of volatile solvents with turn-on and colour change of photoluminescence.